World antimicrobial resistance (AMR) awareness week - Mohammad Mehdi Feizabadi (Iranian Journal of Microbiology)
On the occasion of World Antimicrobial Resistance (AMR) Awareness Week, November 2024, we witnessed a lot of events throughout our country, Iran. Many different specialists throughout the country debated on the current situation, however, no one can predict the future outlook of this ongoing issue. The health policy makers try to find the right solutions for combating the drug-resistant superbugs but they should not ignore Microbiology principles. Carbapenem-resistant Klbesiella pneumoniae infections are definitely the main causes of morbidity and mortality in the Iranian Hospitals. In the current issue of this Journal, Dr. Solgi and his colleagues have raised an important and critical point: New Delhi metallo-beta-lactamase (NDM-MBL). Unfortunately, the number of cases infected with ceftazidime/avibactam-resistant Gram-negative bacteria has increased due to NDM-MBL production (Nearly 87% of K. pneumoniae clinical isolates in Isfahan). Therefore, our country resources are wasted with the current official protocol for administration of ceftazidime/avibactam, despite knowing that NDM-MBL producers are dominant. Physicians should be aware of the current situation of MBL strains in Iran, which is attainable through reviewing works published by Microbiologists in different provinces of Iran.